Religious Freedom in the Global South (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The aim of this book is to create a space for contributions on religious freedom in the Global South. The contributions speak to diverse themes underscoring religious freedom in the Global South including the impact of religious freedom on majority and minority religious communities, the relationship between religious freedom and the state, and the relationship between religious freedom and other fundamental human rights. Through the adoption of inter- and multidisciplinary approaches, and with reference to various religions such as Islam, Hinduism, Sufism, Sikhism, and Christianity, contributors address the themes across several regions in the world including Africa, South Asia, South-East Asia, South America, and Eastern Europe. Depending on the social, legal, and political context and by relying on diverse examples such as the Muslim call to prayer (adhan), domestic violence, animal sacrifice, religious conversions, abortion, the rights of LGBT persons, and religious education in the public sphere, the contributions illustrate how religious freedom can undermine or promote the rights of majority or minority religious communities, and how it can impact on the rights of marginalised members within minority religious communities.